The Association Between Preference Satisfaction and Satisfaction with Overall Care for Nursing Home Residents. Issue 5 (3rd September 2022) - Madrigal, Caroline; Mogle, Jacqueline; Abbott, Katherine; Mills, Whitney L.; Fick, Donna M.; Scanlon, Dennis; Behrens, Liza; Eshraghi, Karen; VanHaitsma, Kimberly
ABSTRACT: The Centers for Medicare and Medicaid Services mandate the provision of person-centered care (PCC), but there is limited evidence on how PCC impacts nursing home (NH) residents' care experiences. This study examined the relationship between n = 163 NH residents' ratings of satisfaction with care related to their preferences and their satisfaction with overall care. Residents with higher preference satisfaction ratings reported significantly higher levels of satisfaction with overall care. Using preference satisfaction ratings has the potential to improve PCC planning and delivery in nursing homes.